2019
DOI: 10.2134/jeq2018.11.0394
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Phosphate Release from Sewage Sludge Ash Using an Ion Sink Assay

Abstract: Thermochemical treatments allow production of sewage sludge ash (SSA) rich in P and low in heavy metals, which could be recycled in agriculture. Our objective was to quantify P release from SSA using ion sink assays and to relate these results to P speciation in SSA and plant P uptake. Anion and cation exchange membranes saturated with different counterions (HCO3, Na, and H) were used to create a gradient in pH, P, or cation concentration between SSA particles and the surrounding solution. Phosphorus speciatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In addition to the traditional methods, novel ones that test P in the soil solution (anion exchange resins, iron-coated filter papers, iron bag, Rhizon soil moisture sampler, Diffusive Gradients in Thin Films, etc.) for assessing the P availability of secondary P fertilizing products have indicated a good correlation with the concentration of P in plants [43][44][45][46][47][48]. Still, the number of those studies is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the traditional methods, novel ones that test P in the soil solution (anion exchange resins, iron-coated filter papers, iron bag, Rhizon soil moisture sampler, Diffusive Gradients in Thin Films, etc.) for assessing the P availability of secondary P fertilizing products have indicated a good correlation with the concentration of P in plants [43][44][45][46][47][48]. Still, the number of those studies is limited.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a large study undertaken by Römer & Steingrobe 35 using sandy and loamy soils showed that maize and winter wheat had a PUE of under 25% when grown on most treated sewage sludge ashes, with only Mg treated sewage sludge having a PUE higher than 50%. Nanzer et al 36 obtained similar results where plants grown on Mg-treated sewage sludge had higher yields and P uptake compared to Ca-treated sewage sludge in an acid soil. The difference is attributed to the higher solubility of Mg phosphate precipitates compared to Ca phosphates.…”
Section: Resultsmentioning
confidence: 73%